Space vectors and pseudo inverse matrix methods for the radial force control in bearingless multi-sector permanent magnet machines - Sala, Giacomo; Valente, Giorgio; Formentini, Andrea; Papini, Luca; Gerada, David; Zanchetta, Pericle; Tani, A.; Gerada, C. (Institute of Electrical and Electronics Engineers, 2018)
Two different approaches to characterize the torque and radial force production in a Bearingless Multi-Sector Permanent Magnet (BMSPM) machine are presented in this work. The first method consists of modelling the motor in terms of torque and force production as a function of the stationary reference frame α-β currents. The current control reference signals are then evaluated adopting the Joule losses minimization as constrain by means of the pseudo inverse matrix. The second method is based on the control of the magnetic field harmonics in the airgap through the current Space Vector (SV) technique. Once the magnetic field harmonics involved in the torque and force production are determined, the SV transformation can be defined to obtain the reference current space vectors. The methods are validated by numerical simulations, Finite Element Analysis (FEA) and experimental tests. The differences in terms of two Degrees of Freedom (DOF) levitation performance and efficiency are highlighted in order to give the reader an in-depth comparison of the two methods.